Heart Team risk assessment with angiography‐derived fractional flow reserve determining the optimal revascularization strategy in patients with multivessel disease: Trial design and rationale for the DECISION QFR randomized trial. Issue 6 (31st March 2022) - Miyata, Kotaro; Asano, Taku; Saito, Akira; Abe, Kohei; Tanigaki, Toru; Hoshino, Masahiro; Kobayashi, Tomoaki; Takaoka, Yoshimitsu; Kanie, Takayoshi; Yamasaki, Manabu; Yoshino, Kunihiko; Wakabayashi, Naoki; et al.
Abstract: In patients with multivessel disease (MVD), functional information on lesions improves the prognostic capability of the SYNTAX score. Quantitative flow ratio (QFR®) is an angiography‐derived fractional flow reserve (FFR) that does not require a pressure wire or pharmacological hyperemia. We aimed to investigate the feasibility of QFR‐based patient information in Heart Teams' discussions to determine the optimal revascularization strategy for patients with MVD. We hypothesized that there is an acceptable agreement between treatment recommendations based on the QFR approach and recommendation based on the FFR approach. The DECISION QFR study is a prospective, multicenter, randomized controlled trial that will include patients with MVD who require revascularization. Two Heart Teams comprising cardiologists and cardiac surgeons will be randomized to select a revascularization strategy (percutaneous coronary intervention or coronary artery bypass graft) according to patient information either based on QFR or on FFR. All 260 patients will be assessed by both teams with reference to the anatomical and functional SYNTAX score/SYNTAX score II 2020 derived from the allocated physiological index (QFR or FFR). The primary endpoint of the trial is the level of agreement between the treatment recommendations of both teams, assessed using Cohen's κ . As of March 2022, the patient enrollment has been completed and 230 patients have been discussed in both Heart Teams. The current trial will indicate the usefulness of QFR, which enables a wireless multivessel physiological interrogation, in the discussions of Heart Teams to determine the optimal revascularization strategy for MVD.